The significance of ANGPTL3 and ANGPTL4 proteins in the development of dyslipidemia in Type 2 diabetes mellitus - Rik Swarnakar; Debadyuti Sahu; Jyotirmayee Bahinipati; Tapaswini Pradhan; Dayanidhi Meher; Rajlaxmi Sarangi; Srikrushna Mahapatra (Journal of Family Medicine and Primary Care)
Background: Dyslipidemia is the leading cause of cardiovascular disease (CVD) in Type 2 diabetes mellitus patients. As a result, it is critical to target and manage the level of atherogenic lipids. Angiopoietin-like proteins 3 and 4 (ANGPTL 3 and ANGPTL 4) play an important role in the intravascular lipolysis of triglyceride-rich lipoproteins by blocking the enzyme lipoprotein lipase. This study aimed to determine the amounts of these angiopoietin-like proteins in T2DM and find their association with dyslipidemia in T2DM. Material and Methods: Sixty-one T2DM patients of age group 25–65 years and 27 healthy age-matched control participants were enrolled in the study. Glycemic status (FBS, PPBS, HbA1C), serum lipid parameters (cholesterol, TG, LDL, VLDL, HDL, Tc/HDL ratio), free fatty acid, serum insulin, and ANGPTL3, 4 were measured. A correlation was found between the ANGPTLs and the above parameters in T2DM patients. Results: Serum ANGPTL3 (P < 0.05) and ANGPTL4 (P < 0.001) were significantly decreased in T2DM. ANGPTL4 was also negatively correlated to PPBS (0.03), HbA1C (P = 0.05), and IR (P = 0.04). However, no such correlation was observed with ANGPTL 3. It was observed that lipid parameters were correlated with ANGPTL3 (LDL (P = 0.03), TC/HDL (P = 0.02)). There was a significant relationship between ANGPTL3 and 4 with FFA (P = 0.001 and P = 0.03, respectively). Conclusion: This study shows that ANGPTL 3,4 may be associated with dyslipidemia in T2DM. ANGPTL4 is more correlated with glycemic status.